The impact of plasma triglyceride and apolipoproteins concentrations on high-density lipoprotein subclasses distribution - Tian, Li (BioMed Central, 2011)
OBJECTIVE: To investigate the effect of triglyceride (TG) integrates with plasma major components of apolipoproteins in HDL subclasses distribution and further elicited the TG-apolipoproteins (apos) interaction in the processes of high density lipoprotein (HDL) mature metabolic and atherosclerosis related diseases. METHODS: Contents of plasma HDL subclasses were quantities by two-dimensional gel electrophoresis associated with immunodetection in 500 Chinese subjects. RESULTS: Contents of preβ(1)-HDL, HDL(3a), and apoB-100 level along with apoB-100/A-I ratio were significantly increased, whereas there was a significant reduction in the contents of HDL(2), apoA-I level as well as apoC-III/C-II ratio with increased TG concentration. Moreover, preβ(1)-HDL contents is elevated about 9 mg/L and HDL(2b )contents can be reduced 21 mg/L for 0.5 mmol/L increment in TG concentration. Moreover, with increase of apoA-I levels, HDL(2b )contents were marginally elevated in any TG concentration group. Furthermore, despite of in the apoB-100/A-I < 0.9 group, the contents of preβ(1)-HDL increased, and those of HDL(2b )decreased significantly for subjects in both high and very high TG levels compared to that in normal TG levels. Similarly, in the apoB-100/A-I ≥ 0.9 group, the distribution of HDL subclasses also showed abnormality for subjects with normal TG levels. CONCLUSIONS: The particle size of HDL subclasses tend to small with TG levels increased which indicated that HDL maturation might be impeded and efficiency of reverse cholesterol transport(RCT) might be weakened. These data suggest that TG levels were not only significantly associated with but liner with the contents of preβ(1)-HDL and HDL(2b). They also raise the possibility that the TG levels effect on HDL maturation metabolism are subjected to plasma apolipoproteins and apolipoproteins ratios.